Pain in South African HIV-positive patients - Mphahlele, Noko Reshoketswe (My University, 2014)
Pain is one of the most frequent and debilitating symptoms in human immunodeficiency virus (HIV) infected individuals. With Southern Africa being the region with the highest population of HIV-infected individuals, I set out to determine whether the pain intensity, prevalence and management strategies that have been reported in other, non-African, countries are similar to that in South African patients. South Africa has eleven official languages, with nine of those being native languages. Also, there is a high level of illiterate people in the country, thus, for better assessment of the pain I translated the Wisconsin Brief Pain Questionnaire into five frequently spoken local languages. Using the translated questionnaires I investigated the prevalence, intensity and management of pain in ambulatory HIV-positive outpatients attending a metropolitan (n = 396) or rural (n = 125) clinic. I also assessed whether this pain changes over time in a subset of 92 metropolitan patients. Seventy-two percent of rural participants and 56% of metropolitan participants had pain at the time of the interview, and this pain was moderate to severe in intensity in 60% of affected rural participants and 59% of affected metropolitan participants. In the rural cohort, use of antiretroviral therapy was independently associated with the reduced risk of pain [prevalence ratio (95% CI): 0.7 (0.5-0.9)] while in the metropolitan cohort increasing age was weakly, but independently associated with having pain [prevalence ratio (95% CI): 1.01 (1.005-1.012)]. Pharmacological management of pain was poor, with 29% of rural participants and 55% of metropolitan participants with pain not receiving any treatment. Of those receiving treatment, no participants were receiving strong opioids, and only 3% of metropolitan participants were receiving a weak opioid. On a positive side, the pain that South African HIV-infected individuals endure decreases over time. Seventy-eight patients out of the subsample cohort consisting of 92 patients reported pain at the time of the first interview. Of the 78 patients who were in pain at visit 1, 48 were still in pain six months later with 36 of those not prescribed any form of analgesics. Thus I found a decrease in moderate and severe intensity pain to mild and moderate pain, respectively, from visit 1 to visit 2. Of the 78 patients that were in pain at visit 1, only 5% received some form of analgesic therapy. Forty-eight of the 78 patients were still in pain six months later, and of those, 25% were being prescribed some form of analgesics at visit 2. There were no changes in the pain-related interference over a six month period in patients who were in pain at visit 1 and visit 2. Therefore, as it has been reported previously for other developed and developing countries, pain in HIV-positive South Africans is common and is under-treated. Also, there are decreases in the pain intensity, pain prevalence, the number of pain sites over a period of six months. These decreases were evident in patients who were on HAART for the duration of six months as compared to those who were not on HAART for six month.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2013
Keywords: HIV-positive persons.; HIV-positive persons - South Africa.